1998
DOI: 10.1038/sj.ejcn.1600598
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, iron status, and hemoglobin concentration in obese dieting women

Abstract: Objective: To determine the relationships between cognitive function and iron status in dieting obese women. Design: Longitudinal weight loss study (repeated measures within-subject design) with 3 weeks of baseline, 15 weeks of 50% caloric restriction, and 3 weeks of weight stabilization. Dietary iron was fed at twice the US Recommended Dietary Allowance with half of the iron from food sources and half from an oral supplement. Setting: This was a free-living study with the exception that subjects came to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 22 publications
(28 reference statements)
2
40
2
1
Order By: Relevance
“…A further 5.4% suffered from iron deficiency with anemia, which is also below the mean for industrialized societies (10.3% in women aged 15-59 years) [1] . Thus, the present study provides no evidence that overweight/mildly obese women are more likely to have a poorer iron status due to poorly controlled diets or sporadic fasting, as mentioned by some authors [4] .…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…A further 5.4% suffered from iron deficiency with anemia, which is also below the mean for industrialized societies (10.3% in women aged 15-59 years) [1] . Thus, the present study provides no evidence that overweight/mildly obese women are more likely to have a poorer iron status due to poorly controlled diets or sporadic fasting, as mentioned by some authors [4] .…”
Section: Discussioncontrasting
confidence: 45%
“…However, dieting can impair iron status in obese women, even when sufficient dietary iron is available [4] .…”
mentioning
confidence: 99%
“…Nevertheless, most of the findings are in agreement and provide us with data with which we can compare our results. With respect to observational studies, Kretsch et al (27) reported a correlation of both hemoglobin and transferrin saturation with sustained attention in obese dieting women, whereas Foley et al (28) found a correlation between iron concentrations (ie, zinc protoporphyrin) and spatial performance in male and female undergraduate students. Our observation of a significant difference in the attention domain between ironsufficient and iron-deficient women is in agreement with these observations.…”
Section: Discussionmentioning
confidence: 99%
“…(2012) Studies related to the impact of hemoglobin levels on mental functioning in adult populations are few and the outcomes are inconclusive 12,13 . Keeping this in view, the present study was designed to assess the possible impact of iron nutritional status on cognitive functioning among dental students between the ages of 18-25 years as the profession of dentistry requires keen recognizing abilities, decision making skills as well as ample physical stamina, which may be impaired by low iron/hemoglobin levels thereby influencing one's ability to be a successful dentist.…”
Section: Introductionmentioning
confidence: 99%